Development of a HOTS-Based Mathematical Abstraction Ability Instrument in Trigonometry Using Riau Islands Province Culture - Dwi Rismi Ocy; Wardani Rahayu; Makmuri Makmuri (Jurnal Gantang, 2023)
The lack of available assessment tools that effectively measure students' ability to think abstractly in mathematics, particularly in trigonometry. Additionally, there is a need to incorporate local culture into the assessment instrument to make the content more relatable and relevant to students in Riau Islands Province. This study is a development study using the Define, Design, and Develop processes from the 4D development model that have been converted to 3D. 3 doctoral lecturers in mathematics education subsequently validate the instruments produced; they are modified in response to their feedback and recommendations. A team of 17 teachers and instructors of high school mathematics validated the results, followed by panelists' validation. The content Validity Ratio (CVR) index value on the panelist's validation of 25 items is greater equals to 0.765. The instrument has been tested on 20th-grade 10th high school students. The results show that the instrument can be used on a large scale, and the instrument with the cultural context of the Riau Islands Province enables students to break down complex problems into simpler components, identify relevant variables, and establish connections between them.